Doenças osteoarticulares e desempenho físico de idosos Brasileiros com idade igual ou superior a 80 anos - dos Santos, Vanessa Ribeiro [UNESP]; Gobbo, Luís Alberto [UNESP]; Christofaro, Diego Giulliano Destro [UNESP]; Gomes, Igor Conterato; Mota, Jorge; Gobbi, Sebastião [UNESP]; Júnior, Ismael Forte Freitas [UNESP] (FapUNIFESP (SciELO), 2016)
Objective: To investigate the physical performance of Brazilian individuals older than 80 years with and without OD. Methods: The sample consisted of 135 individuals (aged > 80 years) of both gender. Identification of osteopenia/ osteoporosis was verified by Dual Energy X-ray Absorptiometry, and the presence of others osteoarticular diseases (OD) was obtained using a questionnaire of morbidities. Physical performance was analyzed by motor tests. Results: Men presented higher proportion of osteopenia/osteoporosis compared to women (p = 0.013). The proportion of older people with arthritis/osteoarthritis for women and men was 33% and 26%, respectively, and with OD in the spine was 19% and 12%, respectively. No significant difference for physical performance, measured by each test and overall score, was observed between groups of OD. According to gender, male with OD presented lower performance in gait speed, balance and overall score (p < 0.05), while older people with osteopenia/osteoporosis are at higher risk for low physical performance (OR 2.73; CI 95% 1.31- 5.66). Conclusion: In conclusion it was verified in older people with age of 80 years or more, a high prevalence of OD, especially in men, and the presence of these diseases interfered negatively their physical performance.
Osteoarticular diseases and physical performance of Brazilians over 80 years old
Keywords: Arthritis; Elderly; Osteoarthritis; Osteoporosis; Physical performance